Efektivitas Pengadaan Aset Kendaraan Dinas Operasional di Sekretariat Daerah Kabupaten Jombang - Annisa Wulandari; Bayu Priambodo (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to determine the effectiveness of operational official vehicle procurement at the Regional Secretariat of Jombang Regency based on the suitability of needs, quality, quantity, and implementation time, as well as its contribution to the smooth execution of government duties and public services. A descriptive qualitative approach was used in this study, with data collected through interviews. The effectiveness of operational official vehicle procurement at the Regional Secretariat of Jombang Regency was analyzed using Sudarmayanti's effectiveness theory, which consists of three indicators. The results show that the procurement of official vehicles at the Regional Secretariat of Jombang Regency has met high-quality standards in accordance with the Regional-Owned Goods Needs Plan (RKBMD). The procurement process adheres to the principles of efficiency, transparency, and accountability, following Presidential Regulation No. 12 of 2021. The effectiveness of the procurement is evident from vehicles that meet high technical specifications, the quantity aligned with operational needs, and timely execution to support the new government in 2025. This reflects the regional government's dedication to implementing professional, effective, and sustainable governance.